Analysis of Related Factors with The Performance of the Midwife in the Handling of Neonatoric Asphycia in the Area of the Health Service of Magelang Regency - Hermani Triredjeki Triredjeki; Che’An Ahmad (Jurnal Ilmiah Kesehatan, 2023)
The infant mortality rate in the Magelang Regency Health Office area will increase in 2020-2022 from 6.34/1000 KH to 7.38/1000 KH with details of the cause of death due to asphyxia neonatorum 27%. In handling neonatal asphyxia, the role of village midwives is needed to help reduce infant mortality. This study aims to determine the factors that influence the performance of midwives in the service of neonatal asphyxia in the Health Office of Magelang Regency. The type of research used is observational which is analytic in nature with a cross sectional approach. Data collection was carried out by interviews using a structured questionnaire that had been tested for validity and reliability. Sixty five respondents were selected purposively with inclusion and exclusion criteria. The analysis used is the Chi Square test and multiple logistic regression. The average age of the respondents was 38 years, 96.9% of the respondents had Diploma III in Midwifery. Most of the respondents (72.3%) had less knowledge, 55.4% had less attitude, 50.8% had less motivation. Most (80%) of the support resources (funds, facilities, infrastructure) are good. Respondents' perception of supervision (52.3%) is good. Most of the respondents (60%) had poor performance in handling neonatal asphyxia. The results of the bivariate analysis showed that knowledge (p = 0.001), attitude (p = 0.0001), motivation (p = 0.0001), perceptions of supervision (p = 0.0001) were related to the performance of village midwives. Multivariate analysis showed that there was a joint relationship between knowledge (Exp.(B) 7.723) and motivation (Exp.(B) 8.324) and the performance of village midwives in handling neonatal asphyxia. The Health Service needs to provide technical guidance on a regular basis in the management of neonatal asphyxia and increase motivation by giving awards to midwives who work well in the service of neonatal asphyxia.